DERAJAT KEJANG DEMAM PADA ANAK BALITAÂ DI RUANG SERUNI RSUD JOMBANG - Prasastia LD, Catur; Marta Ananuri, Ayu (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The impact of febrile seizure when the demands of oxygen are not fulfilled, there can be brain hypoxia and brain damage. If it is let without treatment which is fast and responsive, it will cause the death. The purpose of this study identified degree of febrile seizure in the children whose were 1-5 years old at RSUD Jombang. The research design used descriptive. The population was all of children who are suffering febrile seizure at Seruni Room RSUD Jombang until be obtained sample as many as 30 children whose were 1-5 years old. Data were taken by purposive sampling technique. The result of this study indicated the degree of febrile seizure in the children whose were 1-5 years old at RSUD Jombang. It was founded that most children who had a febrile seizure was the vast majority of children experienced a simple febrile seizures of the complex febrile seizures by the time, the child was in the hospital getting treatment so that the risk of recurrence of febrile seizures were very small. We recommend that health workers provide health education to parents when their child home from the hospital about febrile seizures. So that, parents understand more about how to prevent and cope with febrile seizures in children and can provide appropriate action on their child when the child has a febrile seizure.Keywords: body temperature, febrile seizure, children